1997
DOI: 10.1037/0022-006x.65.3.381
|View full text |Cite
|
Sign up to set email alerts
|

Modeling relapse in unipolar depression: The effects of dysfunctional cognitions and personality disorders.

Abstract: Survival analytic models were used to determine the effects of Axis II pathology and dysfunctional cognitions on depressive relapse in a sample of 50 depressed inpatients followed 33 to 84 months (M = 49.9) postdischarge. In analyses based on follow-up interview measures, expected remission duration among patients without personality disorders was approximately 7.4 times longer than among patients with Axis II comorbidity. Attributional style also accounted for unique variance in the relapse model, with adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
96
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 42 publications
8
96
1
2
Order By: Relevance
“…A third study using 2 year data showed that personality disorders significantly prolonged the time to remission for MDD . That study confirmed the results from earlier work (Ilardi et al, 1997). In general, this literature shows that comorbid personality disorders can negatively affect the course of MDD and that improvements of MDD do not usually affect the course of personality disorders.…”
supporting
confidence: 82%
“…A third study using 2 year data showed that personality disorders significantly prolonged the time to remission for MDD . That study confirmed the results from earlier work (Ilardi et al, 1997). In general, this literature shows that comorbid personality disorders can negatively affect the course of MDD and that improvements of MDD do not usually affect the course of personality disorders.…”
supporting
confidence: 82%
“…BDI-II scores were, on average, in the mildly symptomatic range, similar to other studies which have sampled a remitted depressed adult population (Hart, Craighead, & Craighead, 2001;Ilardi, Craighead, & Evans, 1997). IPDE total dimensional scores were somewhat lower than found previously in a similar population (Hart et al, 2001).…”
Section: Resultssupporting
confidence: 58%
“…These PDs emerged as robust predictors of slowed remission from MDD even when controlling for other negative prognostic predictors. In this ongoing CLPS study, future analyses will attempt to delineate factors that might influence the timing of changes-such as relapses (Ilardi et al, 1997) and associated changes (e.g., life events, treatment, psychosocial functioning)-and how these factors contribute to the longer-term course of depression. Survival curves (time to remission) for major depressive disorder (MDD) as a function of personality disorder comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, but not all, have suggested that PDs may have a negative impact on the course or outcome of Axis I disorders Grilo, McGlashan, & Oldham, 1998). For instance, some research has found that PDs predict development of depression (Alnaes & Torgersen, 1997), poorer response to treatment for depression (Mulder, 2002), and relapse to depression (Hart, Craighead, & Craighead, 2001;Ilardi, Craighead, & Evans, 1997).…”
mentioning
confidence: 99%